Stand-alone polyetheretherketone cages for anterior cervical discectomy and fusion for successive four-level degenerative disc disease without plate fixation - Ahmed M Ashour (Journal of Craniovertebral Junction and Spine, 2020)
Background: Anterior cervical discectomy with fusion became the most frequently performed technique for the treatment of symptoms related to cervical disc prolapse. Multilevel anterior cervical discectomy has been combined with anterior cervical plate application to help maintain the cervical lordosis and enhance fusion. This was associated with more soft-tissue separation and retraction with increased incidence of surgically related complications and postoperative dysphagia.Aim of the Study: The aim of this study is to evaluate the safety and efficacy of the stand-alone cervical polyetheretherketone (PEEK) cages in four-level discectomy and to determine if it is possible to avoid anterior plate fixation and to achieve satisfactory outcomes. Methodology: This is a retrospective study which was performed between June 2011 and December 2018 at one institute. The clinical and radiological data were collected from patients who underwent successive four-level anterior cervical discectomy and fusion with PEEK cages for degenerative cervical disc disease without plate fixation. Results: This study included 66 patients, 35 males and 31 females. The follow-up period was 24 months. Mean Japanese Orthopedic Association scores were 13.3 ± 1.41 preoperative and 15.9 ± 0.86 postoperative (P = 0.046). The cervical curvature index “Ishihara” (ICI) was 9.9 ± 5.90 preoperative and the mean of ICI was 10.5 ± 6.65 postoperative, which is insignificant, P = 0.7). The lordotic curvature according to these results was preserved till the end of the year and half of the follow-up period postoperative. Conclusion: Consecutive four-level anterior discectomy with PEEK cage interbody fusion without plate and screw is a safe and effective procedure in the absence of instability, and it may be a reliable alternative for the treatment of multilevel cervical disc.